Increasing Financial Inclusion for Coffee Farmers through Fintech Education and Implementation in Lembang - M. Yani Syafei; Rahma Wahdiniwaty; Sudadi Pranata (International Journal Of Community Service, 2025)
Financial inclusion plays a crucial role in improving the economic resilience of smallholder farmers, particularly in rural areas with limited access to formal financial services. This community engagement program aimed to enhance financial literacy and promote fintech adoption among coffee farmers in Lembang. The initiative included structured training sessions, fintech demonstrations, and collaboration with agricultural cooperatives to ensure sustainable financial education. The results indicated a significant improvement in farmers’ understanding of financial management, budgeting, and digital financial tools. Many participants successfully adopted mobile banking, digital payments, and fintech-based lending solutions, reducing their reliance on informal credit sources. The involvement of cooperatives facilitated the dissemination of financial knowledge beyond the initial participants, contributing to long-term sustainability. However, challenges such as digital literacy gaps among older farmers and limited internet infrastructure in remote areas were identified as barriers to widespread fintech adoption. To address these issues, continuous financial literacy programs, mentorship initiatives, and infrastructure improvements are recommended. This study highlights the potential of fintech solutions in bridging financial access gaps and empowering rural farmers with better financial decision-making capabilities. Future initiatives should focus on expanding fintech services to include agricultural insurance and investment options, ensuring a more comprehensive approach to financial inclusion in the agricultural sector.